KAJIAN KESESUAIAN DAN DAYA DUKUNG FISIK KAWASAN PANTAI YANAIN DI NEGERI HULALIU KECAMATAN PULAU HARUKUKABUPATEN MALUKU TENGAH - Laisina, Valentino Gloria Giovanni; Lelloltery, Henderina; Puttileihalat, Maya (MARSEGU : Jurnal Sains dan Teknologi, 2024)
This research aims to assess the suitability and physical carrying capacity of Yanain Beach in Hulaliu State, Pulau Haruku District, Central Maluku Regency as a tourist destination. The methodology employed in this study involved a survey, collecting both primary and secondary data through direct field observations. Primary data included visual observations and measurements at Station 1 and Station 2, as well as interviews with visitors to the beach area. Data analysis utilized tourism suitability index and physical carrying capacity of the beach area. Yanain Beach covers an area of 2.14 hectares with a sandy beach width of 18.76 meters, providing ample space for tourist activities. Additionally, it features a relatively shallow depth (1.48 meters), slow current velocity (0.0847 m/s), and high water clarity (>80%), making it an attractive tourist destination. Based on the calculated values, it was concluded that Yanain Beach in Hulaliu Village is "Highly Suitable" for various tourism activities, with an average TSI score of 92.25%. Furthermore, the analysis of the beach's carrying capacity indicated that the area can accommodate 641 people per day for recreation purposes, and 407 people per day for swimming and bathing activities at the beach.